Tobacco And Indian Youth: A Review - Basanta Kumar Choudhury1, K.L. Sushmita2, Santosh Subudhi3, Somalee Mohapatra4, Namrata Mishra2 (Institute of Medico-legal Publications Pvt Ltd, 2020)
In India and the South Asian part of the world use of tobacco is seen for a longtime. If we go back decadesback tobacco is used as a gift to treat the guests and also it was encouraged to use in past times. Sooner whenthe malicious side effects of tobacco were noticed people tried to avoid the consumption of tobacco. Thepsychological mindset of the youth is quite impressionable, seeing the things that the adults do would easilyencourage them to do the same. Thus, this article reviews various forms of tobacco used in our Indian societyand how the government of India is taking action to curb the tobacco abuse